SOME ASPECTS OF THE HISTORY OF EARLY WESTERN EUROPEAN COUNTERPOINT (POLYPHONY IN AQUITAINE IN LIGHT OF HISTORICAL-PHASED APPROACH) (Mūzikas akadēmijas raksti, 2024)
The purpose of this article is to substantiate the hypothesis about blending of stages of oral and written music in medieval polyphony. It is important to properly consider musical systems conditioned by primitive notation. In this case, the method of typological analysis is applied to reveal correlation between categories of the primary and the secondary, to characterize sonority and the ways of intoning, as well as the performers’ goals. The analytical material is presented by examples of Aquitaine polyphony. The period until recently called Limoges school is one of the most intricate in medieval musical history with only a few sources. As respective manuscripts were notated using Aquitaine neumes, polyphony pieces from those should be called Aquitaine.